IMPLEMENTASI ASAS PROPORSIONALITAS DALAM PERJANJIAN TERAPAUTIK DALAM RANGKA MEWUJUDKAN KEADILAN BAGI PASIEN - Alfis Setyawan; Nur Hadiyati (Fakultas Hukum Universitas Islam Malang, 2021)
Therapeutic agreements are agreements made between doctors and patients in general related to the health efforts that will be taken. The practice of therapeutic agreements sometimes raises awareness for patients who have minimal knowledge of medicine and tend to be harmed. This leads to therapeutic agreements needing an in-depth legal review. The issues to be examined are urgency agreements are examined from civil law and the application of the principle of proportionality in therapeutic agreements generally. The research uses normative legal research with conceptual approaches. It is found that the application of the principle of proportionality in therapeutic agreements and the fulfilling of elements in civil law can be an effort to provide justice for all parties both doctors and patients.